The timing of concurrent intrathecal chemotherapy during blinatumomab infusion influences neurotoxicity in pediatric acute lymphoblastic leukemia - Liu, Bingju; Dai, Yunpeng; Liu, Liying; Wang, Qi; Guan, Guotao (Frontiers in Immunology, 2026)
ObjectiveTo assess the safety profile of administering intrathecal (IT) chemotherapy concurrently with blinatumomab in pediatric patients with acute lymphoblastic leukemia (ALL).MethodsThis retrospective analysis included 93 pediatric ALL patients treated between February 2021 and May 2025 who received blinatumomab.ResultsOf the 93 enrolled patients (median [Q1, Q3] age, 6 [4, 12] years), 42 (45%) were given IT chemotherapy concurrently, while the remaining 51 (55%) served as controls. Neurotoxic events occurred in eight patients (8.8%) overall, with no statistically significant difference between the concurrent IT and control groups (12% vs. 6%, p = 0.461). However, receiving IT chemotherapy on Day 1 of blinatumomab was strongly associated with neurotoxicity (OR = 15.6; 95% CI: 2.96–87.8; p = 0.001). Additional univariate predictors included CD4+ T-cell count (OR = 0.03; 95% CI: 0.00–0.50; p = 0.045), serum albumin (OR = 1.17; 95% CI: 1.02–1.39; p = 0.042), and bone marrow blast percentage (OR = 1.05; 95% CI: 1.01–1.09; p = 0.017). Multivariate analysis identified Day 1 concurrent IT administration as an independent risk factor (OR = 12.5; 95% CI: 1.45–131; p = 0.023).ConclusionsInitiating IT chemotherapy on the same day as blinatumomab infusion significantly increases the risk of neurotoxicity in pediatric ALL patients.